Օսմանյան Թուրքիայում հպատակ ժողովուրդների (հայեր, հույներ, հրեաներ) ազգային սահմանադրության եւ կանոնադրությունների հարցի շուրջ - Սիլվինէ Մարկոսյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В статье представлена разработка и утверждение уставов подчиненных народов в Османской Турции, как проявление перестройки национальных администраций подчиненных народов. Были проанализированы существующие различия и сходства между Национальной конституцией Западной Армении, греческим и еврейским уставами. The article reflects on processing and confirming Charters of subordinate nations in the Ottoman Empire, considering national Charters as national departments rebuilding manifestation of the subordinate nations. The national Charter of Western Armenians, which is essentially the result of pressure by European authorities, at the same time, introduced an innovation in the national life of the Armenians — electoral suffrage.
Keywords: Christianity; History of the Armenian Church